2019
DOI: 10.1021/acsami.9b04351
|View full text |Cite
|
Sign up to set email alerts
|

Poly(photosensitizer) Nanoparticles for Enhanced in Vivo Photodynamic Therapy by Interrupting the π–π Stacking and Extending Circulation Time

Abstract: The natural planar and rigid structures of most of the hydrophobic photosensitizers (PSs) [such as tetraphenyl porphyrin (TPP)] significantly reduce their loading efficiencies in polymeric nanoparticles (NPs) because of the strong π−π interaction-induced aggregation. This aggregation-caused quenching will further reduce the quantum yield of singlet oxygen ( 1 O 2 ) generation and weaken the efficiency of photodynamic therapy (PDT). In addition, the small molecular PSs exhibit short tumor retention time and ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…These results showed that the PWG nanostructures display highly effective PDT against tumors,w hich might result from the large amount of tumor accumulation of the PWG nanofibers possessing high 1 O 2 generation capacity. [14] Figure 5d showed that the body weights of the mice in all groups were not significantly different and showed ac ontinued increase during treatment, indicating the high biocompatibility of this PDT system. In Figure S10, the hematoxylin and eosin (H&E) sections of the organs from the mice of the four groups did not show obvious pathological changes,w hich confirmed that we developed ab iocompatible treatment for tumor ablation.…”
Section: Forschungsartikelmentioning
confidence: 92%
See 2 more Smart Citations
“…These results showed that the PWG nanostructures display highly effective PDT against tumors,w hich might result from the large amount of tumor accumulation of the PWG nanofibers possessing high 1 O 2 generation capacity. [14] Figure 5d showed that the body weights of the mice in all groups were not significantly different and showed ac ontinued increase during treatment, indicating the high biocompatibility of this PDT system. In Figure S10, the hematoxylin and eosin (H&E) sections of the organs from the mice of the four groups did not show obvious pathological changes,w hich confirmed that we developed ab iocompatible treatment for tumor ablation.…”
Section: Forschungsartikelmentioning
confidence: 92%
“…[13] Once released in the tumor site,l ow molecular weight photosensitizers tend to quickly diffuse away and get cleared from tumor tissues,c ausing limited tumor accumulation and short retention times,which strongly limit the application of PDT in clinical trials for cancer therapy. [14] Thus,i ti su rgent to develop nanomaterials to overcome this issue.W ang, Lam and co-workers developed several stimuli-responsive in situ self-assembled and transformable peptide-based nanoparticles which underwent at ransformation to fibrillar structures in the tumor microenvironment;these structures performed excellently in tumor imaging and therapy in vivo by blocking for example HER2 dimerization. [7b,15] Compared to traditional nanoparticles, these fibril-transformable nanoparticles possessed prolonged retention time in tumors and thus caused an enhanced photoacoustic imaging signal, selective cytotoxicity against cancer cells and remarkable tumor suppression efficacy in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the tumor retention of nanosystems can be further promoted by using the “passive targeting” effect, which involves surface modification with tumor targeting groups (e.g., peptides, [ 10 ] antibodies [ 11 ] ). Although these approaches have significantly improved the tumor retention of PSs, the therapeutic nanosystems are usually cleared from the tumor site within 1–3 days, [ 7–12 ] which, in many cases, is still not long enough to guarantee efficient PDT. Consequently, phototherapy needs to be carried out soon after the PSs injection, and high doses or multiple injections of PSs are required to treat large or malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Such a polyporphyrin successfully inhibited ACQ and enhanced singlet oxygen ( 1 O 2 ) generation yield, in vitro phototoxicity, and in vivo PDT for anticancer treatment. 29,30 Compared to a cross-linked polyporphyrin, a linear polyporphyrin is more desirable to achieve better spatial segregation and manipulation of cationic charges in precise modification sites. Hence, a cationic and linear polyporphyrin can be considered as an ideal PS-based gene carrier to fulfill all three principles mentioned above including delivery, safety, and therapy.…”
Section: ■ Introductionmentioning
confidence: 99%